Geostationary Communication Satellite Solar Array Optimization Using Gravitation Search Algorithm - Souad Oukil; Abdelmadjid Boudjemai (Journal of Aerospace Technology and Management, 2020)
The preliminary design of geostationary communication satellite solar array is presented in this work. Based on the power requirements, power margin requirements and performance requirements, the number of panels, strings and cells to be used on the solar array were defined. The main objective of this study was to optimize the power generated from the satellite solar array and the extraction of the parameters of a photovoltaic module, which is subject to the space environment and under a series of practical constraints, in order to extract the desired performance parameters for multiobjective functions, taking into account the solstice and equinox periods during temperature operation. A gravitational search algorithm based on the law of gravity and mass interactions was introduced. This algorithm has proved its effectiveness in optimizing system parameters in the literature. From the results obtained in this work, the total power of the optimized system was reduced by 181 W. The degradation and output power characteristics of the solar panels were calculated for different temperature values.